The ecology of sexual dimorphism in size and shape of the freshwater blenny Salaria fluviatilis. Issue 2 (30th June 2017) - Laporte, Martin; Berrebi, Patrick; Claude, Julien; Vinyoles, Dolors; Pou-Rovira, Quim; Raymond, Jean-Claude; Magnan, Pierre; ,
Abstract: Sexual selection is considered the major cause of sexual dimorphism, but recent observations suggest that natural selection may play a more important role in the evolution of sex differentiation than previously recognized. Therefore, studying the trade-offs between natural selection and sexual selection is crucial to a better understanding of the ecology underlying the evolution of sexual dimorphism. The freshwater blenny Salaria fluviatilis, a fish inhabiting lakes and rivers around the Mediterranean Sea, displays strong sexual dimorphism in size, shape, and behavior (i.e., larger body and head size for males and higher swimming requirements for females during the reproductive period). We tested for differences in sexual dimorphism in size and shape between the populations from lake and river habitats with the goal of identifying the trade-offs between natural and sexual selection that underlie variations in sexual dimorphism in this species. Our results show i) differences in sexual size dimorphism (SSizeD) in accordance to Rensch's rule (i.e., larger individuals in rivers associated with higher SSizeD), and ii) a decrease in shape differentiation between males and females in lake populations. Together, this suggests that the different environmental conditions between lake and river habitats (e.g., resource limitations, predation pressure, water velocity) affect the relative importance of sexual selection in the display of sexual dimorphism within the species. This study highlights the importance of considering the environmental conditions to which populations are exposed to better understand the ecology underlying the evolution of sexual dimorphism.